2010
DOI: 10.1007/s10585-010-9363-7
|View full text |Cite
|
Sign up to set email alerts
|

Versican induces a pro-metastatic ovarian cancer cell behavior which can be inhibited by small hyaluronan oligosaccharides

Abstract: The assembly of pericellular matrix containing hyaluronan (HA) and versican has been shown to be a pre-requisite for proliferation and migration of mesenchymal cells. In this study, we investigated whether treatment with recombinant versican could induce the formation of a pericellular matrix by ovarian cancer cells (OVCAR-3, OVCAR-5, and SKOV-3) and promote their motility, invasion, and adhesion to peritoneal cells in vitro. We also determined whether versican-induced pericellular matrix formation and metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 68 publications
3
54
0
Order By: Relevance
“…Recent studies focussing on the tumour microenvironment have identified that the ECM molecule HA, plays an important role in both ovarian cancer invasion and the development of chemotherapy resistance (Ween et al 2011a, Ricciardelli et al 2013. Our studies have confirmed that HA plays an important role in promoting attachment of cancer cells to peritoneal cells via interactions with the HA receptor, CD44 (Ween et al 2011a).…”
Section: :11supporting
confidence: 76%
See 2 more Smart Citations
“…Recent studies focussing on the tumour microenvironment have identified that the ECM molecule HA, plays an important role in both ovarian cancer invasion and the development of chemotherapy resistance (Ween et al 2011a, Ricciardelli et al 2013. Our studies have confirmed that HA plays an important role in promoting attachment of cancer cells to peritoneal cells via interactions with the HA receptor, CD44 (Ween et al 2011a).…”
Section: :11supporting
confidence: 76%
“…Our studies have confirmed that HA plays an important role in promoting attachment of cancer cells to peritoneal cells via interactions with the HA receptor, CD44 (Ween et al 2011a). We have also shown that HA can induce resistance to the chemotherapeutic drug carboplatin and increase the expression of ABC transporters that function as drug efflux pumps in ovarian cancer cell lines (Ricciardelli et al 2013).…”
Section: :11supporting
confidence: 69%
See 1 more Smart Citation
“…Apart from integrins, other ECM adhesion molecules that contribute to cancer migration and invasion involve interactions between hyaluronan (HA) and versican, which can be blocked by small HA oligosaccharides (70). More importantly, there have been several documented studies showing the pivotal role of HA in the adhesion of cancer cells to the peritoneum, which is one of the early events of EOC progression (71).…”
Section: Ecm Components and Cell Adhesion Molecules Assist Cancer Migmentioning
confidence: 99%
“…Inhibition of VCAN expression or function in glioma cells, ovarian cancer cells, or lung cancer cells has been shown to inhibit cell invasion (64)(65)(66). Targeting of VCAN thus provides a potential strategy for suppressing tumor invasion (65,67,68). Our identification of a transcriptional enhancer that is active in fibroblasts may prove useful in understanding Vcan regulation in the context of tumorigenesis and could provide a therapeutic target.…”
Section: Tbx20 Regulates the Endocardial Proliferation And Migratory mentioning
confidence: 99%